The effect of mergers, BOPO, NPF, growth, and the BI rate on murabahah margin income in Islamic mortgage products at Bank Syariah Indonesia - Deni Lubis; Olga Aulia Pranayutantri; Marhamah Muthohharoh (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2023)
This study aims to analyze the effect of mergers, economic growth, the volume of murabaha financing, Bank Indonesia interest rates, and other variables on murabaha income on sharia pawn products at Bank Syariah Indonesia. The results of this study indicate that murabaha margin income is used as the dependent variable in this study. Dummy variables, five independent variables that have a large influence on the results, two independent variables that do not have a significant impact on the results, and one dummy variable are one of the seven independent variables used in this study. The model used is multiple linear regression with the OLS method. The findings of this study indicate that neither inflation nor fluctuations in the volume of murabaha financing have a significant effect on income from murabahah margins. Income from murabaha margins, however, is very negatively affected by non-performing financing (NPF) variables. Operating expenses as a percentage of operating income (BOPO), BI rate, growth, and aggregation dummy all have a large beneficial impact on earnings on murabahah margins.